5th International Electronic Conference on Sensors and Applications 2018
DOI: 10.3390/ecsa-5-05733
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to the Monitoring of Ceramic Surface Quality Using a Low-Cost Piezoelectric Transducer in the Grinding Operation

Abstract: The grinding process is usually one of the last stages in the manufacturing process chain since it can provide superior surface finish and closer dimensional tolerances. However, due to peculiarities of the grinding process, a workpiece material is susceptible to many problems, and demands a reliable real-time monitoring system. Some grinding monitoring systems have been proposed by means of sensors. However, the literature is still scarce in terms of employing time–frequency analysis techniques during the gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The present work is an expansion of the research activities described in Viera et al [16,29], where initial results were presented. Therefore, the scope of this research work is to illustrate a new broader approach for the real-time monitoring system of the surface quality of ground ceramics using the low-cost PZT diaphragm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work is an expansion of the research activities described in Viera et al [16,29], where initial results were presented. Therefore, the scope of this research work is to illustrate a new broader approach for the real-time monitoring system of the surface quality of ground ceramics using the low-cost PZT diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, piezoelectric diaphragms of lead zirconate titanate (PZT) have become popular due to the fact that it has been successfully used in many scientific applications in view of its low cost and excellent sensing capacities [16,17]. The PZT diaphragms have a simple construction consisting of a brass plate on which a ceramic disc is fixed.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study using a low-cost piezoelectric diaphragm and a commercial acoustic emission sensor, along with digital signal processing techniques in the evaluation of the surface quality of ground ceramic workpieces, was developed by Viera et al [21,24]. The results showed that the proposed technique (statistic ROP STFT ) was able to detect roughness variations on the surfaces of the ground workpieces.…”
Section: Traditional Monitoring Techniques Applied To Industrial Pmentioning
confidence: 99%